A RARE INFECTION IN FROG RANA TIGRINA DAUD OF A STREGEID LARVA - PANDEY, K. C.; TYAGI, VINITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
small pharynx of 0.014-0.016 x 0.020-0 022 mm present. Oesophagus short, Records of Indian frogs, acting as intermediate host, in the life cycle of trematodes are meager (Kaw, 1950: Srivastava & Ghosh, 1969; Mukherjee & Ghosh, 1970; Agrawal, 1975). Three stregeid metacercarial cysts, attached to each other, were collected from the intestinal content of a frog, Rana tigrina Daud, out of twenty examined at district Meerut. Since the larva appears new to science, it is described herein as such. Tetracotyle kawin. sp.